Legal Aspects of Moral Rights and Economic Rights in Music Creation Using AI Music Generators - Lili Sekararum Utami; Subianta Mandala; Darwati Darwati (Jurnal Pendidikan Indonesia, 2025)
The advancement of artificial intelligence (AI) technology has had a significant impact across various sectors, including the music industry. One of the latest innovations is the AI Music Generator, which is capable of automatically creating musical compositions without direct human involvement as the creator. However, this development raises various legal issues, particularly concerning moral rights and economic rights in the context of copyright protection for music works produced by AI. This study aims to analyze the legal aspects related to moral and economic rights in the creation of music generated by AI Music Generators. The study also compares copyright regulations in several countries, including Indonesia, the United States, and the European Union, to understand how international and national laws accommodate AI advancements in the music industry. The findings show that, to date, there are no specific regulations governing copyright ownership of AI-created works. This results in legal uncertainty in the distribution of moral and economic rights over AI-generated music. Therefore, legal policy reforms are needed to accommodate AI developments in the music sector while ensuring fairness for creators, AI owners, and music users.